Indological Controversies about the beginning of nāṭya - Gönc Moačanin, Klara (Array, 2007)
Indological controversies about the beginning of natya Though many indologists tried to solve the question of the beginning of natya, there is still no answer to that question. In the last decades scholarly opinion came to conclusion that indologists should renounce of the quest of understanding the prehistory of natya (Renou) and that, as there already existed so many theories about the beginning of natya, there was no need of a new critical overview of the existing theories. I think that further scholarly research is much needed and that the Natyasastra should be taken more into consideration as a valuable source for understanmding the way the art of natya originated.